2018
DOI: 10.1016/j.bbmt.2018.05.020
|View full text |Cite
|
Sign up to set email alerts
|

Preclinical Canine Model of Graft-versus-Host Disease after In Utero Hematopoietic Cell Transplantation

Abstract: In utero hematopoietic cell transplantation (IUHCT) offers the potential to achieve allogeneic engraftment and associated donor-specific tolerance without the need for toxic conditioning, as we have previously demonstrated in the murine and canine models. This strategy holds great promise in the treatment of many hematopoietic disorders, including the hemoglobinopathies. Graft-versus-host disease (GVHD) represents the greatest theoretical risk of IUHCT and has never been characterized in the context of IUHCT. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 50 publications
0
6
0
Order By: Relevance
“…Other canine studies demonstrated long‐term engraftment with either paternal or maternal BM cells, using a combination of IV IUT to induce DST (1.7‐4.8E+8 CD34 cells/kg with 1%‐2% CD3+, achieving 0%‐1.6% chimerism) and postnatal HSPC transplantation (HCT, 2.5‐8.6E+6 CD34 cells/kg at 4‐11m) to boost chimerism to 30%‐50% in 33% of recipients 4 . These demonstrated the advantage of administering a higher IV dose of maternal BM cells (5.7‐17E+8 CD34 cells/kg) at 0.63G (the beginning of immune‐responsiveness) to sustain engraftment at 3%‐39% while circumventing GVHD by controlling the CD3 component 6,33 . This level of engraftment was not repeatable in the NHP model of mIUT, where boluses of 0.2‐1.7E+8 maternal BM cells/fetus resulted only in microchimerism in most organs 16 .…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…Other canine studies demonstrated long‐term engraftment with either paternal or maternal BM cells, using a combination of IV IUT to induce DST (1.7‐4.8E+8 CD34 cells/kg with 1%‐2% CD3+, achieving 0%‐1.6% chimerism) and postnatal HSPC transplantation (HCT, 2.5‐8.6E+6 CD34 cells/kg at 4‐11m) to boost chimerism to 30%‐50% in 33% of recipients 4 . These demonstrated the advantage of administering a higher IV dose of maternal BM cells (5.7‐17E+8 CD34 cells/kg) at 0.63G (the beginning of immune‐responsiveness) to sustain engraftment at 3%‐39% while circumventing GVHD by controlling the CD3 component 6,33 . This level of engraftment was not repeatable in the NHP model of mIUT, where boluses of 0.2‐1.7E+8 maternal BM cells/fetus resulted only in microchimerism in most organs 16 .…”
Section: Discussionmentioning
confidence: 89%
“…4 These demonstrated the advantage of administering a higher IV dose of maternal BM cells (5.7-17E+8 CD34 cells/kg) at 0.63G (the beginning of immune-responsiveness) to sustain engraftment at 3%-39% while circumventing GVHD by controlling the CD3 component. 6,33 This level of engraftment was not repeatable in the NHP model of mIUT, where boluses of 0.2-1.7E+8 maternal BM cells/fetus resulted only in microchimerism in most organs. 16 Although the mechanisms of graft rejection were not studied in the NHP, a brisk immunological rejection was suspected due to minimal donor cells recovered 24h post-IUT.…”
Section: Discussionmentioning
confidence: 96%
“…aIUT produced both poorest DCC and most robust alloresponsiveness, contrasting with data from other IUT models in which allogenic donor cells have a competitive advantage. [32][33][34][35][36] Although reduced MMc was associated with increased Treg and Breg cytokine expression, upregulated Teff and an overwhelmingly proimmune cytokine response were present, expediting allogeneic cell rejection.…”
Section: Discussionmentioning
confidence: 99%
“…This strategy focuses on inducing a graft-versus-hematopoietic effect with the use of donor T cells, but without GVHD. Previous studies in murine, sheep, canine, swine, and non-human primate models emphasized the importance of T cells and demonstrated that approximately 1%-2% donor T cells are felicitous in facilitating donor cell engraftment without GVHD (Crombleholme et al, 1990;Shields et al, 2003;Lee et al, 2005b;Chen et al, 2008;Vrecenak et al, 2018). In addition, using donor T cells presensitized to the recipient with donor HSCs can also provide an engraftment advantage to donor cells without GVHD (Bhattacharyya et al, 2002;Hayashi et al, 2004).…”
Section: Overcoming Immune Barriersmentioning
confidence: 99%